2021
DOI: 10.1039/d1cy00304f
|View full text |Cite
|
Sign up to set email alerts
|

Potential SiX (X = N, P, As, Sb, Bi) homo-bilayers for visible-light photocatalyst applications

Abstract: Low dimensional materials possess a challenge to identify a photocatalyst suitable for photocatalytic water splitting application. We have systematically investigated that SiN, SiP, and SiAs homo-bilayers are efficient for water...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 76 publications
1
10
0
Order By: Relevance
“…2,52 Recently, van der Waals heterostructures based on silicon SiX (X = N, P, As, Sb, Bi) have been investigated in several stacking configurations, in which SiN was proposed for water oxidation applications and SiP for photocatalytic water splitting. 64 Therefore, considering the silicon-based structures investigated here, it is interesting to explore if those systems could be used as building blocks and how their properties would modify with different morphologies. The Si 2 N 2 and Si 2 P 2 bilayers have been considered for UV-light applications due to their wide band gap 19 and as thermoelectric materials at room temperature.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…2,52 Recently, van der Waals heterostructures based on silicon SiX (X = N, P, As, Sb, Bi) have been investigated in several stacking configurations, in which SiN was proposed for water oxidation applications and SiP for photocatalytic water splitting. 64 Therefore, considering the silicon-based structures investigated here, it is interesting to explore if those systems could be used as building blocks and how their properties would modify with different morphologies. The Si 2 N 2 and Si 2 P 2 bilayers have been considered for UV-light applications due to their wide band gap 19 and as thermoelectric materials at room temperature.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Examples of these types of material include phosphorene, antimonene, h-BN, g-C 3 N 4 , MXene, transition metal-based selenides, nitrides, phosphides, group IV-VI compounds, group III-VI compounds, and group VA binary compounds. 7,[13][14][15][16][17][18][19][20][21][22][23][24] In search of efficient materials for the HER, several strategies had been implemented viz. the effect of doping, defect/ vacancy creation, single atom catalysts (SAC), strain modulation and functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…The binary compounds of these elements in both space groups have band gaps ranging from 0.35-5.14 eV and are dynamically stable, making them promising candidates for water splitting applications. Somaiya et al 22,45 explored the strain and thermoelectric properties of these hexagonal SiX (X = group V) monolayers. Additionally, they also explored SiX homo-bilayers for visiblelight photocatalytic water splitting (PWS) and thermoelectric applications, indicating the catalytic inertness of SiP and SiAs towards the OER and a high figure of merit of 1.02 for SiSb.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, silicon phosphide (SiP), as a IV–V 2D semiconductor material with an indirect bandgap in bulk and a direct bandgap in the monolayer, which has attracted increasing attention owing to its tunable bandgap and high carrier mobility (2860 cm 2 ·V –1 ·s –1 ). , Different from black phosphorus, SiP has a much wider bandgap which strengthens its redox ability for photocatalytic reaction as well as its structural stability. More importantly, theoretical calculations have shown that SiP exhibits suitable energy band positions for photocatalytic water splitting and nitrogen fixation, making it a good candidate as a photocatalyst . Thus, it is expected that the SiP would be a metal-free, “green”, and visible-light-responsive photocatalyst.…”
mentioning
confidence: 99%
“…More importantly, theoretical calculations have shown that SiP exhibits suitable energy band positions for photocatalytic water splitting and nitrogen fixation, making it a good candidate as a photocatalyst. 23 Thus, it is expected that the SiP would be a metal-free, "green", and visible-lightresponsive photocatalyst. To date, to the best of our knowledge, there is no prior study regarding the use of SiP as a photocatalyst for photocatalysis.…”
mentioning
confidence: 99%